Limitations of gompertz law, and alternative models for analyzing life data - Kwek, Ee Ling (2008)
This project presents a quantitative approach to disprove Gompertz Law in Mortality Studies and two alternative mathematical models (Lagrange Polynomial Model and B-Spline Model) for better mortality fitting.